MHD DYNAMIC BOUNDARY LAYER FLOW OVER A PLANE PLAQUE - Mebine, Promise (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The problem of MHD dynamic boundary layer fluid sliding flow over a plane plaque is investigated. The von Karman™s integral method is applied to integrating the governing system of partial differential equations over the boundary layer thickness. Quantities of physical interest such as the boundary layer thickness, local or wall shear stress, friction drag force and coefficient of friction drag is derived. Comparisons with available literature give excellent agreements. The applicability of large or small magnetic fields in many industrial and electrical devices leads to the derivation of asymptotic results for the slip velocity. Pictorial representation made to the boundary layer thickness indicates that increasing magnetic parameter increases it as a result of the retarding force. The coefficient of friction drag is analyzed for various values of MHD and velocity slip parameters. It was observed that both the MHD and velocity slip or fluid slide parameters have retarding effect on the coefficient of friction drag, with the MHD playing a much more dominant role.